Ablation characteristics associated with steam pops in ablation index-guided radiofrequency ablation of atrial fibrillation - Wang, Xue-Si; Wu, Ze-Yang; Wu, Qi; Long, De-Yong; Sang, Cai-Hua; Jiang, Chen-Xi; Wang, Wei; Zhao, Xin; Li, Chang-Yi; Yu, Rong-Hui; Liu, Nian; Li, Song-Nan; et al. (Europace (London, England), 2025)
Steam pops present a significant concern during radiofrequency (RF) ablation of atrial fibrillation (AF). It is crucial to analyse the incidence and ablation characteristics associated with steam pops. This study aims to investigate the occurrence and potential predictors of steam pops. This study included 3263 patients with AF who underwent RF ablation. Patients with paroxysmal AF received bilateral circumferential pulmonary vein (PV) ablation, while those with persistent AF underwent additional linear ablation. The ablation parameters at the sites of steam pops were compared to those at adjacent anatomical locations. A total of 81 steam pops (2.5%) with one pericardial tamponade were recorded. Steam pops were observed at liner ablation sites: 6 (0.4%) at the mitral isthmus, 16 (0.9%) at the tricuspid isthmus (CTI), and 7 (0.5%) along the roofline. The most common sites of steam pops were the anterior edge of the left superior PV and the inferior vena cava side of the CTI. The impedance drop was significantly higher (18.2 ± 9.5 Ω vs. 13.5 ± 4.8 Ω, P < 0.001) at steam pop sites. The optimal cut-off points of impedance drop for predicting steam pops were > 9.5 Ω within the first 3 s, > 10.5 Ω within the first 5 s, > 13.5 Ω within the first 10 s, and > 18.5 Ω in the whole ablation, respectively. The incidence of steam pops during ablation of AF is infrequent. Impedance drop is the only ablation parameter that could predict the occurrence of steam pops.